Thrustbelts : structural architecture, thermal regimes and petroleum systems - Nemčok, Michal (Cambridge University Press, 2005)
Thrustbelts are likely to be productive sources of hydrocarbons well into the future. Many new technical tools are enabling new discoveries, or the more efficient recovery of known reserves. The authors provide a comprehensive account of thrust systems, including orogenic thrustbelts, transpressional ranges and accretionary prisms and discuss both thin-skin thrust systems and thick-skin inversion structures. The book includes major sections on the basic concepts, definitions and mechanics of thrust systems, the roles of syn-tectonic stratigraphy and fluid flow in determining structural style, the origins and nature of evolving thermal regimes in thrustbelts, and a thorough analysis of petroleum systems and hydrocarbon plays in thrustbelts. Case studies are presented with discussion of the potential applications of the technique, possible limitations and future developments. A comprehensive database of thrustbelts is available to download. This book will be an invaluable resource for research scientists, oil company managers and students.
Keywords: Thrust faults (Geology); Petroleum -- Geology.; elektronické knihy; electronic books